Odpowiedź :
a)
[tex]-(2x-3)=5x-2\\\\-2x+3=5x-2\\\\-2x-5x=-2-3\\\\-7x=-5\ /\ :\ (-7)\\\\x=\frac57[/tex]
b)
[tex]2x-1+(1-2x)=x\\\\2x-1+1-2x=x\\\\0=x\\\\x=0[/tex]
c)
[tex]-5(2x-7)=4-3(x+5)\\\\-10x+35=4-3x-15\\\\-10x+35=-3x-11\\\\-10x+3x=-11-35\\\\-7x=-46\ /\ :\ (-7)\\\\x=\frac{46}7\\\\x=6\frac47[/tex]
d)
[tex]8(1+3y)-3(y-2)=2y+5\\\\8+24y-3y+6=2y+5\\\\21y+14=2y+5\\\\21y-2y=5-14\\\\19y=-9\ /\ :\ 19\\\\y=-\frac{9}{19}[/tex]
e)
[tex]3(2t+1)-t=2t+2(3-t)\\\\6t+3-t=2t+6-2t\\\\5t+3=6\\\\5t=6-3\\\\5t=3\ /\ :\ 5\\\\t=\frac35[/tex]
Odpowiedź:
a)
- (2x -3) = 5x - 2
- 2x + 3 = 5x - 2
- 2x - 5x = - 2 - 3
- 7x = - 5
7x = 5
x = 5/7
b)
2x-1 +(1 - 2x) = x
2x- 1 + 1 - 2x = x
0 = x
x = 0
c)
- 5(2x-7) = 4 - 3(x + 5)
- 10x + 35 = 4 -3x - 15
- 10x + 35 = - 3x - 11
- 10x + 3x = - 11 - 35
- 7x = - 46
7x = 46
x = 46/7 = 6 4/7
d)
8(1 + 3y) - 3(y - 2) = 2y + 5
8 + 24y - 3y + 6 = 2y + 5
21y + 14 = 2y + 5
21y - 2y = 5 - 14
19y = - 9
y = - 9/19
e)
3(2t + 1 ) - t = 2t + 2(3 - t)
6t + 3 - t = 2t + 6 - 2t
5t + 3 = 6
5t = 6 - 3 = 3
t = 3/5